Gambaran Mutu Pelayanan Kesehatan Gigi dan Kepuasan Pasien Di Poli Gigi Puskesmas Abiansemal IV Badung - Ni Putu Ita Mahayati; Putu Ratna Kusumadewi Giri; I Md Ady Wirawan (School of Dentistry Faculty of Medicine Udayana University, 2021)
Introduction: Community Health Centers need to improve the quality of dental health services to improve patient satisfaction. Aim: The objective of this study is to obtain an overview of the quality of dental health services and patient satisfaction at Dental Poly of Community Health Center Abiansemal IV Badung. The specific objectives of the study are to 1) find out the procedure of dental health services at Dental Poly of Community Health Center Abiansemal IV Badung; 2) obtain an overview of the dimensions of the dental health services quality at Dental Poly of Community Health Center Abiansemal IV Badung; 3) obtain an overview of the characteristics of the patients at Dental Poly of Community Health Center Abiansemal IV Badung; and 4) obtain an overview of patient satisfaction with the dental health services quality at Dental Poly of Community Health Center Abiansemal IV Badung. Method: The research design used is descriptive research with time-sequential sampling. The sample size is determined with the Slovin formula. Results: The results of the study at Dental Poly of Community Health Center Abiansemal IV Badung were the dental health procedures starting from the patient registration to the patient's return, all dimensions of health services quality have been implemented. The majority of patients were 68.4% female, the age group 20-29 years were 34.2%, the senior high school education level was 53.9%, the funding source of BPJS was 90.8% and the frequency of the first visit was 50%. The quality of dental health services is expressed well by 3% of patients, and is expressed very well by 97% of patients Conclusion: According to this study, patients were satisfied with the quality of dental health services at Community Health Center Abiansemal IV Badung. Pendahuluan: Puskesmas perlu meningkatkan mutu pelayanan kesehatan gigi untuk meningkatkan kepuasan pasien. Tujuan: Tujuan penelitian ini adalah untuk memperoleh gambaran tentang mutu pelayanan kesehatan gigi dan kepuasan pasien di Poli Gigi Puskesmas Abiansemal IV Badung. Tujuan khusus penelitian adalah untuk: 1) mengetahui prosedur pelayanan kesehatan gigi di Poli Gigi Puskesmas Abiansemal IV Badung; 2) memperoleh gambaran tentang dimensi mutu pelayanan kesehatan gigi di Poli Gigi Puskesmas Abiansemal IV Badung; 3) memperoleh gambaran tentang karakteristik pasien di Poli Gigi Puskesmas Abiansemal IV Badung; dan 4) memperoleh gambaran tentang kepuasan pasien terhadap mutu pelayanan kesehatan gigi di Poli Gigi Puskesmas Abiansemal IV Badung. Metode Penelitian: Desain penelitian yang digunakan adalah penelitian deskriptif dengan time squential sampling. Ukuran sampel ditentukan dengan rumus slovin. Hasil: Penelitian pada Puskesmas Abiansemal IV Badung memperoleh hasil yakni prosedur pelayanan kesehatan gigi mulai dari pendaftaran pasien sampai dengan kepulangan pasien. Keseluruhan dimensi mutu pelayanan kesehatan telah dilaksanakan. Pasien terbanyak berjenis kelamin perempuan 68,4%, kelompok umur 20-29 tahun sebesar 34,2%, tingkat pendidik SMA sebesar 53,9%, sumber pembiayaan dari BPJS sebesar 90,8%, dan frekuensi kunjungan pertama kali sebesar 50%. Mutu pelayanan kesehatan gigi dinyatakan baik oleh 3% pasien, dan dinyatakan sangat baik oleh 97% pasien. Simpulan: Berdasarkan hasil penelitian dapat disimpulkan bahwa pasien puas terhadap mutu pelayanan kesehatan gigi di Puskesmas Abiansemal IV Badung.